Case report: Long term remission of metastatic sinonasal NUT carcinoma after palliative radiotherapy and immunotherapy in an elderly patient - Ng, Justin K. W.; Wong, Edwin C. Y.; So, Tommy C. Y.; Wong, Raiden T. S. (Frontiers in Oncology, 2025)
NUT carcinoma (NC) is an extremely rare, aggressive malignancy characterized by chromosomal rearrangements in the NUTM1 (nuclear protein in testis) gene. It usually affects younger patients with a median age of diagnosis at 23 years old. The mainstay of treatment consists of combination chemotherapy, surgical resection, and high dose radiation. However, prognosis remains dismal with reported median overall survival of 6.7 months. Literature reporting on use of immunotherapy in head and neck NC is limited. Prolonged remission without aggressive multimodality therapy is rare. We report a case of a 87-year-old woman with metastatic sinonasal NC treated with palliative radiotherapy and pembrolizumab who achieved sustained response 2 years from diagnosis.